EFFECT OF MICRO CREDIT FINANCE ON WOMEN EMPOWERMENT IN CROSS RIVER STATE - Helen Walter Mboto; Takon Samuel Manyo; Nkamare Stephen Ekpo; Effiong Okon Asuquo (International Studies Journal)
Micro credit finance is a source of financial services provided by micro finance institutions (MFIs), for entrepreneurs and small businesses.The Nigerian financial system has been characterized by systematic crises arising from inadequate capital base and poor governance, this has some side effect on poor people who are effectively being denied access to credit.The specific objective was to examine the effect of micro credit finance on women empowerment in Cross River State. Survey design was employed in the study and data were primarily sourced using questionnaire instrument. The population used for the study was two hundred and fifty (250) married women in Cross River State.One hundred and fifty-four(154) married women were randomly selected for the study using Taro Yamane formula. Ordinary least square of simple regression was employed to analyze the effect of independent variables on dependent variable. Based on the results of the analysis, it was revealed that micro credit finance had a positive significanteffect on women empowerment in Cross River State. The study recommended that effective policiesshould be adopted to engender micro finance. Adopting this approach is one of the most important steps in making micro finance gender sensitive. Also, managerial skills enhancement should be broadened to include knowledge and skills competencies for gender analysis in policy.